The cardiotropic properties of ZMEI-3 compound – a potential inhibitor of Epac proteins - S. A. Kryzhanovskii; G. V. Mokrov; I. B. Tsorin; E. O. Ionova; M. B. Vititnova; V. N. Stolyaruk; I. A. Miroshkina; A. V. Sorokina; A. D. Durnev (Фармакокинетика и Фармакодинамика, 2025)
Introduction. It is known that the allosteric effector of cAMP, in addition to protein kinase A, is the Epac regulatory proteins, which in cardiomyocytes play a key role in the electromechanical coupling control and their rhythmic activity. However, under pathological conditions, abnormal activity of Epac proteins is responsible for the hypertrophy and fibrosis of cardiomyocytes and the initiation of cardiac arrhythmias. Objective. To study the cardiotropic activity of the compound N,2,4,6-tetramethyl-N-(pyridin-4-yl)benzolsulfonamide (code ZMEI-3), which potentially has the properties of Epac protein antagonists, in models of cardiac arrhythmias and alcoholic cardiomyopathy ( ACMP).Materials and methods. Experiments were carried out on outbred male rats. The antiarrhythmic activity of the ZMEI-3 compound was assessed in models of aconitine and reperfusion arrhythmias, and the cardioprotective activity in a translational model of ACM, which is formed after 24 weeks of forced intake of 10 % ethanol.Results. Using a model of reperfusion arrhythmias in rats, it was shown that the ZMEI-3 compound (2 mg/kg/day for 7 days i.p.) reduces the incidence of life-threatening arrhythmias, including ventricular fibrillation. In conditions of formed ACMP, the studied compound (2 mg/kg/day for 28 days i.p.) increased the inotropic function of the heart, which was judged by the value of the left ventricular ejection fraction. Histological analysis showed that in conditions of formed ACMP, the ZMEI-3 compound reduces the severity of morphological signs of alcoholic heart damage.Conclusions. Compound ZMEI-3, when used in a course, has a pronounced antiarrhythmic effect and reduces the severity of alcohol-related heart failure.